ChemInform Abstract: Hydrothermal Crystal Growth and Structure Determination of Double Hydroxides LiSb(OH)6, BaSn(OH)6, and SrSn(OH)6. Issue 50 (16th December 2014) - Mizoguchi, Hiroshi; Bhuvanesh, Nattamai S. P.; Kim, Young‐Il; Ohara, Satoshi; Woodward, Patrick M.
Abstract Colorless single crystals of (III) and (VI) are grown hydrothermally and the crystal structures are determined by single crystal XRD.